Memahami Konteks Kesopanan Kata “Sampèyan”: Perspesktif Masyarakat Madura - Darul Hikmah (Journal of Social, Culture, and Language, 2024)
This article discusses the perspective of Madurese people in terms of the politeness context of the word ‘sampèyan’ that they use in communication. It discusses who and under what circumstances or situations the word ‘sampèyan’ is used by the Madurese, and how their views are related to the values of modesty attached to the word. By using questionnaire and interview methods, the results of the study show that the word ‘sampèyan’ is commonly used by Madurese people (who use Madurese in their daily life) to parents, teachers, older people, foreigners who just met and known, and to people who are respected, such as community leaders (klebun, belater, camat, regent). However, if the word ‘sampèyan’ is used together with Bahasa Indonesia, it will have an essence and sense (meaning) that are different from the original essence of the Madurese language. In general, the word ‘sampèyan’ can be used in both formal and informal situations. Additionally, associated with the values of politeness that apply to the culture and social norms of the Madurese community, most Madurese people believe that the word ‘sampèyan’ can still be categorized in polite language groups, because according to the language level of Madurese it belongs to the engghi-enten language group and is still appropriate to be used to people they respect. Even though basically there are still higher levels, for example the words ‘panjenengan’ and ‘ajunan’ to show politeness, the word ‘panjenengan’ is only used specifically for the Kyai or Ulama’ and his family, and the word ‘ajunan’ is commonly used together with the word ‘Allah’. However, the results of the study also show that the word ‘sampèyan’ would be disrespectful if it is used roughly to ridicule and harass others because these attitudes are categorized as the attitudes of cangkolang (bad attitudes) and are not acceptable in the social norms of the Madurese community.Key Words: Politeness Context, ‘Sampèyan’, Madurese Language, Madurese Community